Geographic differences in the unpaid caregiver experience from the National Study of Caregiving (NSOC) - Mara Rosenberg; Elizabeth Eckstrom (James Cook University, 2020)
Introduction: The objective of this cross-sectional, descriptive study was to identify unpaid caregiver differences in demographics, competing work responsibilities, support, health, caregiver burden, and interaction with healthcare professionals in US metropolitan and non-metropolitan settings. Methods: This study leveraged the nationally representative survey of older adults and their unpaid caregivers residing in the USA: the 2017 National Health and Aging Trends Study and National Study of Caregiving. Participants were unpaid caregivers for community-dwelling older adults. Results: A total of 2278 unique unpaid caregivers corresponding to 1431 care recipients were investigated for this study. Non-metropolitan caregivers had significantly lower income than their metropolitan counterparts, were more likely to be married or have a partner, missed less work, and, when traveling to provide care, traveled on average fewer minutes than metropolitan caregivers. However, there were no significant differences in relationship to caregiver, impact on primary work responsibilities, financial assistance, resource utilization or access, caregiver burden, relationship with primary care providers, or self-rated caregiver health. Conclusion: Non-metropolitan caregivers experience lower income with possible greater familial support, but despite the financial disparities do not have higher caregiver burden, poorer self-rated health, or differences in other important measures. Additional studies that further divide the non-metropolitan cohort into more refined categories by population and with larger sample sizes are essential for designing policy and programs to learn from rural caregivers and build resilience among all care providers.